Cultural differences in using a telephone answering machine : views on conveying information or maintaining relationships - Mathoho, Evelinah (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPhil (General Linguistics))--University of Stellenbosch, 2009.